Species Composition of Rotifers in a Tropical Lotic Freshwater Ecosystem in South - Eastern Nigeria. - Keziah , Ibemenuga Nwamaka,; Chioma , Obi Valentina; Chukwuemeka , Nwosu Moses (African Journal of Education,Science and Technology (AJEST), 2016)
Fortnightly samples of rotifers were collected from Okpu Stream for two seasons (wet and dry seasons) using plankton net with 55 mm mesh size. Ten species of rotifers composed of 91 individuals belonging to eight families and two orders were collected from all the study stations. Stations 1, 2 and 3 had the overall percentage abundance of 52.75%. The most abundant and diverse family was Brachionidae which was represented by three species encountered in the study. The most abundant species was Brachionus sp. which occurred most in stations 2 (7,25.93%) and 3 (7,14.58%) with overall percentage composition of 17.58%. The least rotifer species in Okpu Stream was Euchlanis sp. (Family Euchlanidae) which was recorded only in stations 1 and 3. Margalef’s taxa richness index was highest in station 1 and least in station 2. Shannon’s index of diversity was maximum in station 3 and least in station 1. Evenness had its highest value in station 3. Dominance index which was highest in station 2 was least in station 3. Bellinger’s coefficient showed that stations 1 and 3 and stations 2 and 3 were significantly similar in trend with each other while stations 1 and 2 were dissimilar. The composition and density of rotifers are influenced by both biotic and abiotic factors. The low abundance of rotifers in station 1 may be due to factors such as fast water current. The ability of rotifers to undergo initial migration which minimizes competition through niche exploitation and food utilization, could be probably the reason for their dominance in aquatic environments. The significantly higher diversity in station 3 is a reflection of an ecologically favourable environment. This is justified by the high evenness. The result of the study showed that biotic and abiotic factors, short development rates and vertical migration influence the composition and density of rotifers